COVID-19 and women's mental health during a pandemic – A scoping review - Nileswar Das; Preethy Kathiresan; Pooja Shakya; Siddharth Sarkar (Indian Journal of Social Psychiatry, 2023)
The novel coronavirus disease (COVID-19) has infected more than 10 million people globally, and it caused more than 500 thousand deaths. Researchers have highlighted the need for early detection and intervention for psychological ill effect of the pandemic on various population subgroups. Women may be more vulnerable in such a crisis phase. This review addresses the mental health needs of women and the kind of interventions needed to cater to their various psychological issues. All existing literature was searched using PubMed, Google Scholar, and Medline databases for articles published on mental health aspects of women during COVID-19 pandemic. Only English language articles published till June 15, 2020, were considered for the review. Data were extracted by the authors from the selected articles, and the findings were synthesized in a narrative format. From the available literature, following themes were identified for further discussion: sexual health and contraception, pregnancy, lactation, domestic abuse, female healthcare workers, women with pre-existing mental illness, women with substance use disorders, homeless women, refugees, and professional sex workers. Studies have reported a higher burden of mental health issues in females than male counterparts and an increase in domestic violence and crises for those at-risk (such as refugees and women with pre-existing illnesses). Women mental health is compromised in many aspects due to COVID-19 pandemic. Findings stress upon the increased need for early detection and prompt intervention for women in the community to alleviate the long-term psychological consequences of this pandemic.